2002
DOI: 10.4269/ajtmh.2002.66.157
|View full text |Cite
|
Sign up to set email alerts
|

Detection by polymerase chain reaction of Schistosoma mansoni DNA in human serum and feces.

Abstract: Abstract. A novel method for the detection of Schistosoma mansoni in human samples that is based on the amplification of a highly repeated DNA sequence has been developed. By use of simple DNA extraction techniques and a rapid 2-step polymerase chain reaction (PCR), it was possible to amplify S. mansoni DNA in human fecal and serum samples. The high sensitivity of the approach enabled the detection of the parasite DNA in fecal samples containing as few as 2.4 eggs per gram of feces, which makes it 10 times mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
178
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(188 citation statements)
references
References 20 publications
6
178
0
4
Order By: Relevance
“…Molecular tools such as conventional PCR and improved DNA amplification methods have been shown capable of detecting schistosome DNA in a variety of samples. A highly repetitive, 121-base pair (bp) sequence has been used to detect DNA from S. mansoni and S. haematobium in stools, serum, urine, and plankton samples (Pontes et al 2002;Sandoval et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular tools such as conventional PCR and improved DNA amplification methods have been shown capable of detecting schistosome DNA in a variety of samples. A highly repetitive, 121-base pair (bp) sequence has been used to detect DNA from S. mansoni and S. haematobium in stools, serum, urine, and plankton samples (Pontes et al 2002;Sandoval et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pontes et al (2002) reported the first use of PCR for the diagnosis of Schistosoma mansoni DNA in faecal samples. High sensitivity and specificity rates were observed by this (Pontes et al 2003) and another group (Allam et al 2009) when compared to routine parasitological examination according to the Kato-Katz method (Katz et al 1972).…”
mentioning
confidence: 99%
“…The first study conducted with fecal samples and serum revealed that the conventional PCR can detect 2.4 fg of DNA of S. mansoni per gram of feces, which makes this method more sensitive than the KatoKatz method 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Primers that amplify a 121 bp tandem repeat DNA fragment of the S. mansoni genome were used for the amplification of this region previously cited by PONTES et al 15 . Bovine Serum Albumin (BSA) (SIGMA, USA) was also added in order to neutralize the action of any inhibitors that could be present at the fecal samples 11 .…”
Section: Dna Extraction From Feces Artificially Marked With S Mansonmentioning
confidence: 99%